Fundamental study of “Lumipulse Presto IL-2R” reagent for measuring soluble interleukin-2 receptor with Lumipulse L2400 - FUKUDA, Tetsuya; NAKADA, Yumeto; ICHIKAWA, Hitomi; MOTOKURA, Toru; NOGAMI, Satoshi; WATANABE, Kanako (Japanese Journal of Medical Technology, 2020)
The levels of the soluble interleukin-2 receptor in serum are elevated in non-Hodgkin’s lymphoma and adult T-cell leukemia/lymphoma and reflect disease activity, so they are used for the assessment of treatment response, auxiliary diagnosis, and follow-up. Since the reagent “Lumipulse Presto IL-2R” that can be used with Lumipulse L2400 was developed this time, a basic study was carried out to introduce the reagent. Good results were obtained for within-run precision, between-day precision, dilution linearity, detection limit, and quantification limit. No effects of coexisting substances or container types were found. The correlation coefficient with “STACIA CLEIA IL-2R” was as high as 0.995, the regression equation was y = 1.17x − 34.33, and no extremely deviated sample was found. In conclusion, because of its good performance, it was suggested that the reagent can be introduced.